Free Vibrations of a Tapered Cantilever Beam With Eccentrically Concentrated Masses and Intermediate Supports - Auciello, N.M.; Bellès, P.M.; Filipich, C.P. (Engineering Transactions, 1997)
The dynamic behaviour of beams with linearly varying cross-section, concentrated masses and intermediate supports has been investigated by means of two exact approaches. In the first case, a general purpose variational method (the so-called Whole Element Method) has been employed, whereas the second approach is classically expressed in terms of Bessel functions. The agreement between these different methods of analysis is illustrated by means of numerical examples.